Empowering the Student through Social Media and Financial Management Plan Templates for Universities in Southeast Asia - Febrilia, Ika; Ratna Anggraini; Shandy Aditya; Tuty Sariwulan; Agung Wahyu Handaru; I Gusti Ketut Agung Ulupui; Puji Wahono; Ati Sumiati; Rida Prihatni; Suherdi; Indra Pahala; Destria Kurnianti (Talenta Publisher, 2024)
Planning from various aspects is crucial in running a business. Planning is done so that an entrepreneur can achieve optimal results and profit. One type of planning that can be utilized in line with the increasingly widespread development of digital marketing is from the side of Social Media and the Financial Management Plan. But unfortunately, not many entrepreneurs, either those who are just starting a business or are currently running a business, apply this type of planning. In fact, by using good planning, an entrepreneur can maximize brand promotion and financial management that they manage. The community service team provides templates and training on the utilization/use of the Social Media Plan and Financial Management Plan Templates to students interested in entrepreneurship (studentpreneurs). The training was conducted through Zoom Meetings at three universities in Southeast Asia (Universitas Negeri Jakarta – Indonesia, Universiti Malaysia Sabah – Malaysia, and Valaya Alongkorn Rajabhat University – Thailand). As many as 85.7% of participants have never used a template similar to a Social Media Plan; 2) There are 77.1% of participants who have never used a template such as a Financial Management Plan; 3) 100% of participants felt that the two templates were handy, and they were interested in using the templates.